تصميم واعادة تاهيل شارع ابو اكتيلة - الهرش, عبد الرحمن (جامعة بوليتكنك فلسطين - مباني, 2019)
This project aims to design and rehabilitate a road in the city of Hebron and continue to the municipality of Hebron, where this street is the main street linking the peace street area Abu Kittila area and the University of Jerusalem Open and the area of Abu Dajan other areas and easy access, and the length of about 1500 m. Summarizing the importance of the street is one of the important streets in the city and needs to be rehabilitated with its residential neighborhoods as well as schools and several wedding halls as well as connect to the area of Al Quds Open University. The project includes the works of surveying the proposed street path as well as the engineering design of the road, the preparation of the executive plans and the development of individual and layer of the pebbles and individual and the layer of asphalt, as well as the rehabilitation of the water network in the street commensurate with the needs of the region of water.
CD , no of pages 128 , مباني 26/2019
Keywords: الطرق - تأهيل; الطرق - تصاميم